Multiple-soliton solutions and analytical solutions to a nonlinear evolution equation - Kaplan, Melike; Ozer, Mehmet Naci (Springer Science and Business Media LLC, 2017)
The mathematical modelling of physical systems is generally expressed by nonlinear evolution equations. Therefore, it is critical to obtain solutions to these equations. We have employed the Hirota’s method to derive multiple soliton solutions to (2+1)-dimensional nonlinear evolution equation. Then we have studied the transformed rational function method to construct different types of analytical solutions to the nonlinear evolution equations. This algorithm provides a more convenient and systematical handling of the solution process of nonlinear evolution equations, unifying the homogeneous balance method, the mapping method, the tanh-function method, the F-expansion method and the exp-function method.
Keywords: 16. Peace & justice